Conservative surgery for stage IC2 mucinous borderline ovarian tumor: a five-year follow-up case report - Utami, Tofan Widya; Nasution, Hiro Hidaya Danial; Oktalia, Arisda; Kusuma, Fitriyadi; Purwoto, Gatot (Faculty of Medicine Universitas Indonesia, 2025)
Mucinous borderline ovarian tumors (MBOTs) represent a significant portion of all borderline ovarian tumors, including variants such as microinvasion and intraepithelial carcinoma, which have a higher recurrence risk. Conservative surgery is recommended for patients with MBOTs seeking fertility preservation, despite remaining a debated option to reduce recurrency. This case highlighted successful MBOT management using conservative surgery with unilateral salpingo-oophorectomy, providing insights into optimal recurrence control. A 30-year-old woman presented with abdominal enlargement, with imaging revealed a large right ovarian mass suspected to be malignant. A left salpingo-oophorectomy was performed, with final histopathology confirming MBOTs with microinvasion and intraepithelial carcinoma. No malignancy was found in the peritoneal fluid, and no adjuvant therapy was given due to fertility preservation reasons. No recurrence after 5 years of follow-up. This report highlights the potential of conservative surgery as a fertility-preserving option for young patients with stage IC2 MBOTs.